(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article discusses how we transform artistic experience into writing, reaching the performance dimension of this preliminary act (Turner apud Dawsey, 2005). From the friction between body/writing unveiled here, he suggests what he calls an artist/researcher of fiction (Lyra, 2011), a kind of cartographer who traces landscapes in the relationship with the self/otherness, generate electrifying moments of an academic f(r)ictional writing. It is necessary to emphasize that the framework of this text is based at the Center for Anthropology, Performance and Drama (Napedra/2005-2013); in the experiences with the subject taught by me in the graduate programs in arts at UERJ, UDESC and UFRN (2017-2019); and finally, in the production of articles, dissertations and theses developed with the research group MOTIM - Myth, Rite and Feminist Cartography in the Arts.